TUITION FEES, HOSTEL CHARGES IN IPTA TO REMAIN THE SAME - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
31 March 2015 The tuition fees and cost of accommodation in all 20 public institutions of higher learning (IPTA) in the country will remain unchanged even after the implementation of the Goods and Services Tax (GST) on April 1.